Abdominal adhesions in gynaecologic surgery after caesarean section: a longitudinal population‐based register study. (14th June 2017) - Hesselman, S; Högberg, U; Råssjö, E‐B; Schytt, E; Löfgren, M; Jonsson, M
Abstract : Objective: The aim of the study was to evaluate the association between abdominal adhesions at the time of gynaecologic surgery and a history of caesarean delivery, and to investigate obstetric factors contributing to adhesion formation after caesarean section (CS). Design: Longitudinal population‐based register study. Setting: Sweden. Population: Women undergoing benign hysterectomy and/or adnexal surgery in Sweden, 2000–2014, with a previous delivery during 1973–2013 ( n  = 15 479). Methods: Information about abdominal adhesions during gynaecological surgery, prior medical history, pregnancies and deliveries were retrieved from Swedish National Health and Quality registers. Main outcome measures: Adhesions. Results: In women with previous CS, adhesions were present in 37%, compared with 10% of women with no previous CS [odds ratio (OR): 5.18, 95% confidence interval (CI): 4.70–5.71]. Adhesions increased with the number of caesarean sections: 32% after one CS; 42% after two CS and 59% after three or more CS ( P  <   0.001). Regardless of the number of CS, factors at CS such as age ≥35 years (aOR: 1.28, 95% CI: 1.05–1.55), body mass index (BMI) ≥30 [adjusted OR (aOR): 1.91, 95% CI: 1.49–2.45] and postpartum infection (aOR: 1.55, 95% CI: 1.05–2.30) increased the risk of adhesions. Conclusions: Presence of adhesions in abdominal gynaecological surgery is associated with women's personal history of caesarean delivery. The number of caesarean sections was the important predictor of adhesions; advanced age, obesity and postpartum infection further increased the incidence. Tweetable abstract: Repeat caesarean, age, obesity and infection increased the risk of pelvic adhesions after caesarean section. Tweetable abstract: Repeat caesarean, age, obesity and infection increased the risk of pelvic adhesions after caesarean section.